2000
DOI: 10.1016/s0042-6989(00)00085-7
|View full text |Cite
|
Sign up to set email alerts
|

Location cue validity affects inhibition of return of visual processing

Abstract: Inhibition-of-return is the process by which visual search for an object positioned among others is biased toward novel rather than previously inspected items. It is thought to occur automatically and to increase search efficiency. We examined this phenomenon by studying the facilitative and inhibitory effects of location cueing on target-detection response times in a search task. The results indicated that facilitation was a reflexive consequence of cueing whereas inhibition appeared to depend on cue informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 14 publications
12
60
0
1
Order By: Relevance
“…If the cue is made predictive, then the situation moves into the realm of associative learning, which could reduce or eliminate the possibility of observing habituation. In accordance with this notion, Wright and Richard (2000) found that when the cues were made predictive, the IOR observed on "same" trials was reduced. The fact that the IOR effect was not totally eliminated could have been due to incomplete learning across trials, or it could have been due to the effect of habituation on early trials before the participant had enough experience to learn of the association.…”
Section: Specific Predictionssupporting
confidence: 56%
“…If the cue is made predictive, then the situation moves into the realm of associative learning, which could reduce or eliminate the possibility of observing habituation. In accordance with this notion, Wright and Richard (2000) found that when the cues were made predictive, the IOR observed on "same" trials was reduced. The fact that the IOR effect was not totally eliminated could have been due to incomplete learning across trials, or it could have been due to the effect of habituation on early trials before the participant had enough experience to learn of the association.…”
Section: Specific Predictionssupporting
confidence: 56%
“…A multitude of factors have been shown to influence the effect of stimulus cues on RT, including response task (e.g., Lupiáñez et al, 1997), the presence of distractors (Lupiáñez & Milliken, 1999), the number of potential target locations (Birmingham, Visser, Snyder, & Kingstone, 2006), the informative value of the cue (Wright & Richard, 2000), the range of cue-target SOAs used (Cheal & Chastain, 2002), the probability of the target being presented at a short or long SOA (Milliken et al, 2003), and the emotional valence of cues (Fox, Russo, & Dutton, 2002). What is less understood is how these factors interact.…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 1, exogenous cues were used that are considered to cause automatic attention shifts (Klein, 2004;Marzouki et al, 2007). However, it is often argued that exogenous cues may also induce endogenous control to some extent when they are informative (Doallo et al, 2004;Müller & Rabbitt, 1989;Wright & Richard, 2000). The aim of Experiment 4 was to test whether a texture advantage is also observed without endogenous control being involved.…”
Section: Methodsmentioning
confidence: 99%
“…However, since the magnitude of the cueing effect increases also with increasing informativeness of a peripheral cue, it has been argued that an endogenous component may be involved in exogenous cueing as well (Doallo et al, 2004;Müller & Rabbitt, 1989;Wright & Richard, 2000).…”
Section: Peripheral and Central Spatial Cueingmentioning
confidence: 99%